Marketing Mix and Repurchase Intention of Cafe Industry During Covid-19: A Statistical and Data Mining Analysis - Alfonsius, Alfonsius; Depari, Genesis Sembiring; Huang, Jen Peng (Jurnal Minds: Manajemen Ide dan Inspirasi, 2021)
The COVID-19 pandemic has hit the world and bring unprecedented changes to all industries, including the Micro Small Medium Entrepreneur (MSME) of coffee shop businesses. This study aimed to determine the effect of the marketing mix on customer satisfaction to increase repurchase intention in modern coffee outlets. In addition, statistical modeling, segmentation analysis, and variables weighting using Support Vector Machine were performed. Eventually, product, price, and place positively and significantly affect customer satisfaction, while the promotion does not. Customer satisfaction was found to increase the repurchase intention of the customers. The segmentation analysis and SVM weighting attributes support the product quality as crucial to the marketing mix. It is implied that marketers should devise a marketing approach differently to different clusters since each cluster has distinct characteristics.